2011
DOI: 10.3390/s110504899
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Electronic Nose as a Screening Tool for the Recognition of Durum Wheat Naturally Contaminated by Deoxynivalenol: A Preliminary Approach

Abstract: Fungal contamination and the presence of related toxins is a widespread problem. Mycotoxin contamination has prompted many countries to establish appropriate tolerance levels. For instance, with the Commission Regulation (EC) N. 1881/2006, the European Commission fixed the limits for the main mycotoxins (and other contaminants) in food. Although valid analytical methods are being developed for regulatory purposes, a need exists for alternative screening methods that can detect mould and mycotoxin contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 23 publications
(22 reference statements)
0
40
0
Order By: Relevance
“…In particular, several authors highlighted the potential of the NIRS methodology as a fast and nondestructive tool for the detection of mycotoxins at contamination levels lower or close to the maximum permitted limit set by the EU (Pettersson and Aberg, 2003;De Girolamo et al, 2009). Methods using the EN were developed by several authors for high throughput screening of DON contamination in durum wheat (Olsson et al, 2002;Campagnoli et al, 2011;Lippolis et al, 2014), indicating that a robust and suitable electronic nose method is able to discriminate wheat samples at contamination levels close to the DON maximum permitted limit set by the EU.…”
Section: Mycotoxin Analysis In Feedstuff As a Tool To Control And Evamentioning
confidence: 99%
“…In particular, several authors highlighted the potential of the NIRS methodology as a fast and nondestructive tool for the detection of mycotoxins at contamination levels lower or close to the maximum permitted limit set by the EU (Pettersson and Aberg, 2003;De Girolamo et al, 2009). Methods using the EN were developed by several authors for high throughput screening of DON contamination in durum wheat (Olsson et al, 2002;Campagnoli et al, 2011;Lippolis et al, 2014), indicating that a robust and suitable electronic nose method is able to discriminate wheat samples at contamination levels close to the DON maximum permitted limit set by the EU.…”
Section: Mycotoxin Analysis In Feedstuff As a Tool To Control And Evamentioning
confidence: 99%
“…Some are advanced enough for field studies and have already reached the stage of commercialization, some are at a transition phase between research and application to analysis of food/feed samples, other still have to face the challenge of validation by multiple laboratories. A list of the emerging rapid methods for mycotoxin analysis is reported in Table 2 Keshri & Magan, 2000;Olsson et al, 2002;Presicce et al, 2006;Cheli et al, 2009b;Campagnoli et al, 2011. (Maragos, 2004;Krska & Welzig, 2006;Zeng et al, 2006;Goryacheva et al, 2007;Maragos & Busnam, 2010). The most known rapid screening methods for mycotoxin detection, especially for the screening of raw materials, are antibody-based methods, ELISA test.…”
Section: Rapid Methods For Mycotoxin Analysismentioning
confidence: 99%
“…Results obtained indicated that the EN equipped with ten MOS (Metal Oxide Semiconductor) sensors array allows the classification of naturally contaminated samples on the basis of DON content into three classes on the basis of the European Union limits for DON in unprocessed durum wheat: (a) non-contaminated; (b) contaminated below the limit (DON < 1,750 μg/kg); (c) contaminated above the limit (DON > 1,750 μg/kg); with a validated prediction error rate of 0% when a 20-sample dataset was considered. (Campagnoli et al, 2011). The same model was used with a 122-sample dataset, 9 contaminated and 113 non-contaminated samples, more faithfully reproducing a real-life situation characterised by unbalanced classes.…”
Section: The Analytical Approaches Miming Senses: the Example Of Elecmentioning
confidence: 99%
See 2 more Smart Citations